Defining Love According to the Teachings of Saint Porphyrios Kafsokalyvitis: Terms, Concept, Content - Ion Marian Croitoru; Gabriel Victor Bâclea (Acta Universitatis Sapientiae: Philologica)
This study delves into the profound conceptualization of love as depicted in Christian theology, particularly through the teachings of Saint Porphyrios of Kafsokalyvia. It explores the evolution of the term “love” from its origins in the Greek language and early Christian writings to the intricate theological expositions by the Church Fathers, with a focus on the contemporary insights of Saint Porphyrios. Despite his lack of formal education, Saint Porphyrios brought a refreshing and experiential perspective to the theological understanding of love. His teachings, characterized by a profound understanding and personal experience of divine love, offer insightful reflections on its transformative power. Saint Porphyrios articulates love not merely as an ethical imperative but as the essence of Christian life, embodying the union with God and theosis. Through a comparative analysis, this study aims to delineate how Saint Porphyrios’s theology of love aligns with, and expands upon, the traditional Christian understanding of love, offering both a continuity with and a deepening of this central theological concept.